Aktualisasi Kaidah al-Ḥājah Tunazzalu Manzilah al-Ḍarūrah pada Akad Istiṣnā’ Paralel - Nurhikmah Huswat; Muhammad Shiddiq Abdillah; Riska Riska (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The study aims to determine the Actualization of al-Ḥājah Tunazzalu Manzilah Al-Ḍarūrah’s rules (Necessity is treated as emergency) in parallel istishna’sale and purchase. This research is employs a qualitative descriptive research approach focused on the analysis of manuscripts and texts,utilizing normative and analytical methods. From the research findings it was discovered that the application of the principle of al-Ḥājah Tunazzalu Manzilah Al-Ḍarūrah in parallel istiṣnā’contracts has been actualized by observing that initially, the legality of parallel istiṣnā’contracts was prohibited due to certain transaction modes not conforming to the provisions of Islamic commercial law. For instance, a party acting as Ṣāni’ to sell goods without prosessing them. Or when acting as the manufacturer, not meeting the criteria as a genuine producer because they require someone else to fulfill the order. The principle in Islamic jurisprudence of al-Ḥājah Tunazzalu Manzilah Al-Ḍarūrah explains that urgent needs criteria can occupy an emergency position, specially primary or fundamental needs. For example, humans require housing to ensure safety and security in their lives but lack funds to purchase a home and have no other means available. In such conditions, parallel istiṣnā’ contracts are permissible. This akigns with the principle of al-Ḥājah Tunazzalu Manzilah Al-Ḍarūrah, which elucidates the position where needs can occupy an emergency situation. The implications of this research are to strengthen Islamic legal theory, provide practical guidance in the Islamic financial sector, address contract limitations, and offer boundaries and understanding of the provisions set by Islamic law.